Spa Center as the Economic Engine of the Municipal Business Ecosystem: Case of Banja Koviljača Organizational Network - Aleksandar Jokić; Mladen Čudanov (Balneo and PRM Research Journal, 2024)
This paper addresses the role of the Spa Health Resort as the Economic Engine of the Mu-nicipal Business Ecosystem. Usualy a single larger enterprise drives the local economy at the municipal level, and in the case of Serbia that company has often been from heavy in-dustries. For many transitional economies, local communities have been supported by the main municipal organization, identified in the literature under the terms economic engine, anchor, driver, powerhouse, catalyst, hub or lifeline. Most literature defines it as a compa-ny that plays a pivotal role in propelling municipal economic growth and development, acting as the source of economic stability and resilience within the municipality. Our re-search is based on dataset gathered from the Serbian Chamber of Commerce, extracted from the annual financial and business reports of 80,737 companies and sole entrepre-neurs in Serbia from 2013 to 2022 and supplemented by detailed insights into business reports of hypothesized economic engine. Our findings support the hypothesis that Spe-cialized Rehabilitation Hospital Banja Koviljaca's acts as economic engine for the region. Conclusion is that investment in balneo industry returns mutlifold benefits of different categories to the community and the state.